2020
DOI: 10.1038/s41746-020-00321-3
|View full text |Cite
|
Sign up to set email alerts
|

Virtual care models for cancer survivorship

Abstract: Virtual care models for cancer survivorship are needed to support patients living with the chronic effects of cancer treatment, while increasing health system capacity. Characteristics that may be critical to their success have not been adequately studied. This scoping review summarizes previous efforts to virtualize survivorship care to inform future innovations in the field. Four databases were searched for articles published before January 2020, and 24 articles that met selection criteria were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…There is plenty of evidence for the benefits of virtual care which have shown successful application of technology in palliative care, survivorship care and symptom management. 58 Benefits for the patient include reduced travel times, 9 reduced costs associated with travelling, reduced waiting times and reduced impact of travel on symptoms. 10 They may feel more comfortable receiving their consultation in the comfort of their own home.…”
Section: Introductionmentioning
confidence: 99%
“…There is plenty of evidence for the benefits of virtual care which have shown successful application of technology in palliative care, survivorship care and symptom management. 58 Benefits for the patient include reduced travel times, 9 reduced costs associated with travelling, reduced waiting times and reduced impact of travel on symptoms. 10 They may feel more comfortable receiving their consultation in the comfort of their own home.…”
Section: Introductionmentioning
confidence: 99%
“…The datedness of the data, which were collected over 4 years ago, was another limitation. A scoping review suggested that future virtual survivorship care models may benefit from integrating existing health systems and services, repurposing common technologies, involving a variety of health professionals, and engaging patients and caregivers from diverse communities (16). While cancer patients prefer treatment cost information (17), the results of this study indicate that cancer patients who experienced distress or cognitive decline during the cancer treatment preferred searching not only for official information or systematically constructed web apps, but also for more interactive information, including the details of daily life and feelings during cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] As a first step in the design phase, we recently conducted a scoping review of existing virtual care models for cancer survivorship. 39 Simultaneous to this work, we have started to review current data inputs to the Ned platform with the goal of establishing clinical cutoffs for the algorithm. This formative work will inform the creation of a draft decision tree used to algorithmically triage patients in the Ned Clinic.…”
Section: Methodological Approachmentioning
confidence: 99%